Construction, Validity, Reliability and Effectiveness of the Psycho-Educated Module Management of Forgiveness - Salmah, Binti Mohamad Yusoff; Alyeca, Eric; Nur Akalili Khairah, Binti Ishak (Universitas Negeri Padang (UNP), 2019)
This study is aimed at developing and testing the Application of Forgiveness Management Module on University Malaysia Sarawak (UNIMAS) trainee counselors. The main focus of the study is focused on the module development process and the effect of the module on the emotional, cognitive and behavioral aspects of an individual. The study was conducted using a qualitative and quantitative combination method. The sample of the study consisted of 8 UNIMAS counseling students. The Instrument Level of Anger Scale (LAS) and Tendency Forgive Scale (TTFS) are used to identify the appropriate study sample to follow this module. The built-in Forgiveness Management module has a high authenticity value of 82.2%. In addition, the reliability test of this module has a high coefficient of Cronbach's Alpha coefficient of 0.884. This proves that participants have learned new knowledge better understanding the concept of forgiveness than before following the modules that have been conducted.